2013
DOI: 10.1364/oe.21.002727
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional dielectric phoxonic crystals with network topology

Abstract: We theoretically demonstrate the existence of simultaneous large complete photonic and phononic bandgaps in three-dimensional dielectric phoxonic crystals with a simple cubic lattice. These phoxonic crystals consist of dielectric spheres on the cubic lattice sites connected by thin dielectric cylinders. The simultaneous photonic and phononic bandgaps can exist over a wide range of geometry parameters. The vibration modes corresponding to the phononic bandgap edges are the local torsional resonances of the diel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…For gold spheres with radius close to half a micron (see Figure 1F), the gaps are predicted at around 1550 nm for light and close to 10 GHz for sound [48]. Similar simultaneous complete phononic and photonic band gaps where also predicted for simple cubic lattices of dielectric spheres connected with dielectric cylinders [49]. Here we should note that by proper engineering of the incoming optical and elastic waves it is also possible to achieve simultaneous localization of the two fields inside partial gaps occurring for certain lattice direction and/or polarization [50].…”
Section: D Phoxonic Crystalssupporting
confidence: 69%
“…For gold spheres with radius close to half a micron (see Figure 1F), the gaps are predicted at around 1550 nm for light and close to 10 GHz for sound [48]. Similar simultaneous complete phononic and photonic band gaps where also predicted for simple cubic lattices of dielectric spheres connected with dielectric cylinders [49]. Here we should note that by proper engineering of the incoming optical and elastic waves it is also possible to achieve simultaneous localization of the two fields inside partial gaps occurring for certain lattice direction and/or polarization [50].…”
Section: D Phoxonic Crystalssupporting
confidence: 69%
“…[45][46][47] In addition, we can also use the topology optimization to design PnC bandgaps with the ultra-low mid-frequencies for low frequency sound insulation. 60 Moreover, the topology optimization combined with the symmetry reduction may be suitable for the PxC bandgap engineering 34,[48][49][50][51][52][53][54][55][56][57][58] to construct more PxCs with a strong photon-phonon interaction. This interesting problem is the subject of our ongoing research.…”
Section: Conclusion Remarksmentioning
confidence: 99%
“…Maldovan et al [2,3] theoretically demonstrated the existence of photonic and phononic bandgaps in a two-dimensional (2D) photonic crystal (PTC) for the first time. Since then, several structures have been studied in order to demonstrate the opening of simultaneous PTBGs and PNBGs [4][5][6][7][8][9]. Different kinds of PXC-based devices have also been proposed, including PXC waveguides [10,11], sensors [12][13][14][15], mode converters [16], and diodes [17].…”
Section: Introductionmentioning
confidence: 99%